Representações irônicas da brasilidade em André Sant’anna - Silva, Ari Denisson da (2017)
This work consists in a critical analysis of a part of the work of Brazilian writer André Sant’Anna (1964-), especially of his novel O Paraíso é bem bacana (2007) and his short stories book O Brasil é bom (2014). We start by reflecting about questions related to the elements usually taken as a reference to the building of an official discourse about Brazil and its people. At this point, we counterpose the ideas of Sérgio Buarque de Holanda (1936) and Jessé Souza (2009; 2012) about Brazilians.The latter’s analysis on Brazilian social classes will serve also to understand representations of poverty and middle class adopted by Sant’Anna in the works listed. Then, we proceed to the relation of O Paraíso é bem bacana events and characters to issues of our times. After, we analyse the meanings produced by names, slangs and accents as represented on the mentioned work, through the study of Hudinilson Urbano (2000) on orality and literature and the one of Lauro José da Cunha (2006) on the presence of the English language on people’s designations in Brazil. Finally, we observe the components able to receive an ironic/ludic interpretation in O Paraíso é bem bacana and O Brasil é bom, as well as the problems that can result of a probable humouristic approach of certain issues, taking as references Lélia Parreira Duarte (2006), Muecke (1982), Minois (2003), Linda Hutcheon (2000) and Lars Elleström (2002).